Lanthanide Identity Governs Guest‐Induced Dimerization in LnIII[15‐MCCuIIN(L‐pheHA)‐5])3+ Metallacrowns. Issue 70 (5th November 2021) - Sgarlata, Carmelo; Schneider, Bernadette L.; Zito, Valeria; Migliore, Rossella; Tegoni, Matteo; Pecoraro, Vincent L.; Arena, Giuseppe
Abstract: Series of lanthanide‐containing metallic coordination complexes are frequently presented as structurally analogous, due to the similar chemical and coordinative properties of the lanthanides. In the case of chiral (Ln III [15‐MC Cu II N(L‐pheHA) ‐5]) 3+ metallacrowns (MCs), which are well established supramolecular hosts, the formation of dimers templated by a dicarboxylate guest (muconate) in solution of neutral pH is herein shown to have a unique dependence on the identity of the MC's central lanthanide. Calorimetric data and nuclear magnetic resonance diffusion studies demonstrate that MCs containing larger or smaller lanthanides as the central metal only form monomeric host‐guest complexes whereas analogues with intermediate lanthanides (for example, Eu, Gd, Dy) participate in formation of dimeric host‐guest‐host compartments. The driving force for the dimerization event across the series is thought to be a competition between formation of highly stable MCs (larger lanthanides) and optimally linked bridging guests (smaller lanthanides). Abstract : The formation of metallacrown compartments in neutral aqueous solution can be templated by an anionic guest, for example, muconate. As demonstrated by calorimetric and NMR techniques, metallacrowns containing larger or smaller central lanthanides only form monomeric host‐guest complexes, whereas intermediate lanthanides uniquely form dimeric host2 ‐guest compartments.